2023
DOI: 10.1111/1365-2664.14444
|View full text |Cite
|
Sign up to set email alerts
|

Non‐neonicotinoid pesticides impact bumblebee activity and pollen provisioning

Abstract: Bees are essential pollinators of crops and wild plants and their ability to forage and pollinate are key aspects of their behaviour. Bee populations are under threat, with the use of insecticides a contributing factor. Most research has focused on neonicotinoid insecticides and bee mortality, and little is known about impacts on bee foraging and delivery of pollination services. However, other insecticide classes, such as organophosphates and pyrethroids, are increasingly used globally, but little is known ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Complementary to the lethal effects, B. terrestris individuals showed sublethal effects after insecticide treatment, but significantly less often than most other species in our study. Even when only a small percentage of bees experience sublethal effects after lambda-cyhalothrin exposure, it may still be potentially relevant in the field; bumble bees that were exposed to the insecticide in a semi-field study showed changes in pollen foraging behavior 51 , an indication for sublethal effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complementary to the lethal effects, B. terrestris individuals showed sublethal effects after insecticide treatment, but significantly less often than most other species in our study. Even when only a small percentage of bees experience sublethal effects after lambda-cyhalothrin exposure, it may still be potentially relevant in the field; bumble bees that were exposed to the insecticide in a semi-field study showed changes in pollen foraging behavior 51 , an indication for sublethal effects.…”
Section: Discussionmentioning
confidence: 99%
“…Bee species like honey bees that prefer mass-flowering crops may even be sprayed while foraging on these crops. We did not address exposure routes in our study but semi-field experiments with two of our tested species have shown that these aspects (e.g., multiple spraying) can modulate bee vulnerability to lambda-cyhalothrin (reducing pollen foraging 51 , inducing an excitatory effect 52 ). The availability of life history trait data of wild bee species is still too limited to use them as predictors in analysis; potentially important traits (such as e.g., grooming behavior 76 or hairiness 77 ) may not have been studied yet, or traits are solely estimated via congeneric representatives rather than being empirically measured 78 80 .…”
Section: Discussionmentioning
confidence: 99%